Density and Comparative Refractive Index Study on Mixing Properties of Binary Liquid Mixtures of Eucalyptol with Hydrocarbons at 303.15, 308.15 and 313.15 K - Sangita Sharma; Pragnesh B. Patel; Rignesh S. Patel; J. J. Vora (E-Journal of Chemistry)
Density and refractive index have been experimentally determined for binary liquid mixtures of eucalyptol with hydrocarbons (o-xylene,m-xylene and toluene) at 303.15 K, 308.15 K and 313.15 K. A comparative study of Lorentz-Lorenz (L-L), Weiner (W), Heller (H), Gladstone-Dale (G-D), Arago-Biot (A-B), Eykman (Eyk), Newton (Nw), Eyring-John (E-J) and Oster (Os) relations for determining the refractive index of a liquid has been carried out to test their validity for the three binaries over the entire mole fraction range of eucalyptol at 303.15 K, 308.15 K and 313.15 K. Comparison of various mixing rules has been expressed in terms of average deviation. From the experimentally measured values, refractive index deviations at different temperatures have been computed and fitted to the Redlich-Kister polynomial equation to derive the binary coefficients and standard deviations.